Doping and doping control in Europe performance enhancing drugs, elite sports and leisure time sport in Denmark, Great Britain, East and West Germany, Poland, France, Italy - Spitzer, Giselher (Meyer & Meyer Sport, 2006)
Here is a survey of, arguably, the biggest threat ever to modern sport: doping. "Doping and Doping Control" reveals the historic course of change and traces the destructive results of doping. It is divided into several regional sections which shed light on the practice of deception in sport through pharmaceutical manipulations, its impact on different societies, and the use of various kinds of drugs and methods. There will be much future work within the EC to combat doping and drug abuse in elite and leisure sports which needs to be fully understood by many of those involved in the sports industry. This volume is an excellent primer and starting point for understanding the issue.